(untitled) (مجلة الفاروق للعلوم, 2026)
The gap between software developers and users remains a persistent challenge despite numerous attempts to address it. This study explores the various dimensions of this gap, including differences in mindset, culture, and communication. It categorizes the gap into nine types, ranging from perspective and ownership gaps to communication and credibility gaps. The study emphasizes the cultural divide as a significant contributor to this problem and highlights the power imbalances that can further hinder effective communication. Efforts to narrow this divide frequently revolve around the promotion of active user involvement in the software development process. However, the effectiveness of these initiatives is contingent upon meticulous attention to a complex interplay of technical and political factors. The study also explores innovative approaches, such as video analysis and clear representations, to enhance understanding between stakeholders. This paper underscores the ongoing challenges in communication and understanding between software developers and users and highlights the need for improved communication, cultural sensitivity, and user participation to address these issues successfully.